Implementation of Cervical Cancer Early Detection Program with IV A Test Method in Cilegon City in 2022 - Melisa Charoline Rembet; Mardiati Nadjib (Ridwan Institute, 2023)
Background: With the high number of cancer cases and deaths and the continued increase in cancer financing, which has caused a number of countries, including Indonesia, to continue to struggle to reduce the impact of cancer, the things that must be done are detection, screening, and treatment, as well as palliative care, which are key components of the response to cancer. Early detection is a major step toward increasing the chances of cancer survivors becoming survivors. The achievement of early detection of cervical cancer in Indonesia in 2019–2021 is still low, at 6.83%, or as many as 2,827,177 women aged 30–50 years have undergone early detection of cervical cancer with the Visual Acetate Inspection (IVA) method. Banten Province only reached 5.61%, which means that it is below the average achievement of Indonesia, and Cilegon City is also still low in the achievement of early detection of cervical cancer in 2021, which is 1.2%. The purpose of this study is to determine the picture of the implementation of the cervical cancer early detection program with the IVA method in Cilegon City and identify obstacles that arise in its implementation. Method: This research is qualitative research with a descriptive approach. Data collection techniques include in-depth interviews, group discussion forums, and document review. Results: The results showed that the availability of SOPs, facilities, and infrastructure that support the implementation is not yet balanced between human resources and the target of the cervical cancer early detection program. There are constraints in the process of implementation, recording, and reporting, as well as low differences in perception in calculating the target achievement of the cervical cancer early detection program. Conclusion: The implementation of the early detection program in all Public Health Center in Cilegon City in 2022 is in accordance with the policy, even though there are still obstacles in its implementation, both passively and actively, so that achievement is still very low.